Smart Calculator 1.0 / Siti Noor Dina Ahmad ... [et al.] - Ahmad, Siti Noor Dina; Mohamed, Nadiah; Yaacob, Nurul Aityqah; Mahayadin, Mahfuzah; Rusli, Nur Ida Aniza; Zulkifle, Farizuwana Akma; Sahrom, Nor Ashikin; Mohd Ruslan, Siti Zaharah; Ismail, Norul Fadhilah; Othman, Norlida; Andu, Yusrina; Ahmad, Mardiana (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Smart Calculator 1.0 was organized by the College of Computing, Informatics and Media Studies UiTM Negeri Sembilan Kampus Kuala Pilah on December 9 2022. A total of 150 students were involved, including Pre-Science, STEM C, and Pre-Academy of Islamic Contemporary Studies. The session was conducted by Siti Noor Dina binti Ahmad from our department. In this program, the students are taught to use the correct method of basic mathematical operations in scientific calculators. They are also asked to apply the method in answering questions, especially in exams. Positive feedback was also given by the student involved, and they suggested that this program should be continued in the future.